Integration of Zeolite Membrane Bioreactor With Granular Sludge-Based Anammox in High-Efficiency Nitrogen Removal From Iron Oxide Red Wastewater - Feng, Xing-Hui; Wang, Xiao-Jun; Li, Hai-Xiang; Zhang, Hai-Ya; Zhu, Zong-Qiang; Liang, Yan-Peng; Dong, Kun; Zeng, Hong-Hu (Frontiers in Microbiology, 2022)
Acquisition of stable nitritation and efficient anammox play a crucial role in partial nitritation (PN) combined with anammox for nitrogen removal from ammonium-rich wastewater. Due to the limitation of ammonia-oxidizing bacteria (AOB) enrichment and nitrite-oxidizing bacteria (NOB) control in traditional membrane biological reactor (MBR), it can result in a lower nitrite production rate (NPR) and unstable PN, eventually reducing the nitrogen removal rate (NRR) via PN-anammox. In this study, we developed a zeolite membrane biological reactor (ZMBR) to enhance the PN of iron oxide red wastewater (IORW), in which the biofilm derived from the zeolite surface can provide free ammonia (FA)-containing microenvironment for AOB enrichment and NOB inhibition. The results showed that ZMBR can tolerate a higher influent nitrogen loading rate (NLR) of 2.78 kg/(m3⋅day) in comparison to the traditional MBR [2.02 kg/(m3⋅day)] and the NPR in ZMBR and traditional MBR were 1.39 and 0.96 kg/(m3⋅day), respectively. The mass concentration ratio of NO2--N/NH4+-N ranged from 1.05 to 1.33 in ZMBR, suggesting a suitable condition for nitrogen removal via anammox. Subsequently, the domesticated granular sludge obtained from a paper-making wastewater treatment was used as the carrier of anammox bacteria to remove nitrogen. After 93 days of operation, the NRR was observed to be 2.33 kg/(m3⋅day) and high-throughput sequencing indicated that the relatively higher abundance (45.0%) of Candidatus Kuenenia stuttgartiensis was detected in the granular sludge of the bottom part of the reactor, which can produce more proteins and lipids, suggesting a good settleability. Overall, this study provides a high-efficient method to control PN and domesticate anammox for nitrogen removal from IORW.